Atmospheric patterns for heavy rain events in Calabria - S. Federico; E. Avolio; L. Pasqualoni; C. Bellecci (Natural Hazards and Earth System Sciences, 2008)
This study investigates the atmospheric pattern circulations associated with heavy rainfall (HR) days in Calabria, southern Italy, and contributes to the understanding of the dynamical mechanisms that produce those events. Heavy rainfall days are extracted from the raingauge database of the "Protezione Civile Regionale", which has more than a hundred pluviometric stations for the period 1999–2007 (eight years). To study the synoptic atmospheric circulations associated with HR we use the Regional Atmospheric Modeling System (RAMS) gridded data field of 925 hPa and 500 hPa geopotential height. First the number of variables is reduced by principal component analysis (PCA), then a cluster analysis (CA) is applied on those new atmospheric variables and eleven atmospheric patterns are obtained. Clear associations emerged between each of the circulation types and rainfall patterns over Calabria for HR days. These associations can be explained by the interaction between the complex orography of the region, the sea and the synoptic scale flow.